Influence of Manure Type and Bedding Material on Carbon Content of Particulate Organic Matter in Feedlot Amendments Using 13C NMR-DPMAS. Issue 1 (2nd January 2018) - Miller, Jim; Hazendonk, Paul; Drury, Craig
ABSTRACT: Feedlots in southern Alberta apply composted (CM) or stockpiled (SM) manure with straw (ST) or wood-chip (WD) bedding to cropland, but few studies have examined the effect of manure type and bedding material on carbon composition of these feedlot amendments prior to land application using solid-state 13 C NMR-DPMAS (nuclear magnetic resonance-direct polarization, magic angle spinning). The particulate organic matter fraction was extracted from four amendment treatments (CM-ST, CM-WD, SM-ST, SM-WD) to avoid possible paramagnetic interference from considerable mineral soil in the manure from the unpaved feedlot. The hypothesis was that O-alkyl C of POM should be lower for more decomposed manure types (CM than SM) and bedding materials (ST than WD), and that alkyl C, aromatic C, carboxyl C, aromaticity, and alkyl:O-alkyl (A:O-A) ratio should be greater for the more decomposed amendments. The C composition of all feedlot amendments was dominated by aromatic C (8%–14%) and O-alkyl (7%–14%) C and had considerable less contribution from carboxyl (2%–4%) and alkyl C (1%–3%). The manure type hypothesis was supported for O-alkyl C (but not for the other three C groups), aromaticity, but not the A:O-A ratio. The bedding hypothesis was supported for O-alkyl C, aromaticity, and A:O-A ratio, but not for alkyl C, aromatic C, and carboxyl C. A decrease in O-alkyl C, increase in aromaticity, and increase in A:O-A ratio (bedding only) with more decomposed manure types or bedding materials suggested that these 13 C NMR parameters may have potential to evaluate the maturity and stability of composted feedlot manures.